PENGARUH PERSONALITY TERHADAP KEAHLIAAN AUDITOR DALAM PENGGUNAAN KOMPUTER (Students' Journal of Accounting and Banking, 2012)
This study aims to determine and analyze whether computer anxiety, computer attitude, math anxiety affects keahliaan auditor in using computers in public accounting firm and BPKP in Semarang. The data used are the primary data, a survey method that is done sending or distributing the questionnaire to the respondent or in this case the auditor who worked at the office of public accountants and BPKP. Population and sample in this study is the auditor who worked in the office of public accounting and BPKP in Semarang. Researchers used a sampling technique convinience sampling, this techique is based on convinience for the researchers in obtaining the respondents due to limitations of the sample and obtaining the respondents were 90 respondents. Test equipment used in this study is by multiple regression analysis.The results of the study of the 3 Variable; independently indicate that personality factors such as computer anxiety and no significant positive effect, computer attitude has positive and significant, math anxiety and a significant positive effect on keahliaan auditor in using computers.Keywords: End User Computing (EUC), Personality and Self- Efficacy